PENGARUH UPAH TERHADAP TURNOVER INTENTION KARYAWAN TEXTILE INDUSTRY: STUDI KASUS PADA PT. HEGARMANAH LESTARI - Versanudin Hekmatyar; Nabiela Rizki Alifa (FEBI UIN Sunan Gunung Djati Bandung, 2022)
Human capital is an important asset for the company and the presence of a high-productivity human capital plays an important role in the success of the company. Therefore, if a company has a high employee turnover rate, the company's performance can be disrupted. The Central Statistics Agency (BPS) reports that the textile industry contributed 6.56% to the non-oil and gas processing industry's Gross Domestic Product (GDP) in the second quarter of 2022. Work activity in the textile trading line has a relatively low level of turnover intention and this study is examined to validate the cause. This study aims to describe the effect of wages on employee turnover intention at PT Hegarmanah Lestari. Data was collected using a quantitative approach and presented descriptively. The results of the study show that there is a significant influence between wages on the turnover intention of PT Hegarmanah Lestari employees. In simple terms, it can be said that PT Hegarmanah Lestari has a relatively low level of turnover intention due to the implementation of wages according to established and generally accepted standards.